PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, LEVERAGE DAN KOMITE AUDIT TERHADAP INCOME SMOOTHING - Saputri, Evita; Febyansyah, Andar (LPPM Institut Pendidikan Nusantara Global, 2023)
This research is to analyze the effect of company size, profitability, leverage and audit committee on income smoothing. The population in this study are property and real estate sector companies listed on the IDX for 2020 – 2022. The data used in this research is secondary data in the form of financial reports obtained through the Indonesian Stock Exchange (IDX) website. The sample selection in this study used a purposive sampling technique. This study uses quantitative methods with the analysis technique used is descriptive statistical analysis and multiple linear regression analysis. The results of this study indicate that firm size, profitability, and leverage have an effect on income smoothing and audit committees have no effect on income smoothing. Income smoothing is a management action to stabilize income by moving income from years with high profits to years of periods of income that are less profitable.